Online adaptive decision fusion based torque ripple reduction in permanent magnet synchronous motor - Erken, Faruk; Oksuztepe, Eyyup; Kurum, Hasan (Inst Engineering Technology-Iet, 2016)
In this paper, new methods for reducing the torque ripple in permanent magnet synchronous motor are proposed. The methods are based on injection of appropriate current harmonics to motor by using adaptive decision fusion algorithms. Three different methods are used in determining injection of current harmonics based on q-axis current, q-axis voltage and reference value of the q-axis current. In these methods, the decision values are linearly combined with weights, which are updated online according to an active fusion method, based on performing orthogonal projections onto convex sets describing these values. The validity of the proposed methods is tested with experimental studies under different operating conditions.
Keywords: Minimization; Drives; Pmsm; Machine; Scheme